Arbitration in domestic and international takeovers & mergers of companies - Ambaras Khan, Mushera Bibi; Arif Zakaria, Mohd Radhuan (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Takeovers and mergers are complex business transaction especially when they take place cross-border. Due to its complex nature, it is inevitable that some takeovers and mergers deals result in disputes. Takeovers and mergers can be successful by implementing a problem solving system that deals with a dispute at an early stage. This corporate exercise also involves a lengthy procedure. Disputes may thus arise at different stages of the corporate exercise; the very initial stage of takeovers and mergers involving the due diligence process itself frequently gives rise to disputes. Many disputes also arises at postclosing stage involving representations and warranties. It is also possible for disagreement and disputes to arise in relation to ancillary agreements related to intellectual property issues and management agreements. Arbitration has emerged as a preferred method to resolve takeovers and mergers related disputes. This paper discusses the importance of arbitration at various stages of takeovers and mergers. The paper detailed out the disputes at various stages of takeovers and mergers. It then examined the role arbitration can play at the various stages involving specific problems and complications related to takeovers and mergers. The paper highlights the advantages of arbitration and examines its effect on takeovers and mergers of companies.